Preparation and Thermoelectric Properties of Si-Doped Tetrahedrites Cu12Sb4-ySiyS13 - Kwon, Min-Cheol; Kim, Il-Ho (Korean Journal of Metals and Materials, 2022)
Si-doped Cu12Sb4-ySiyS13 (y = 0.1-0.4) compounds were prepared using solid-state synthesis. Each specimen consisted of a single tetrahedrite phase with a densely sintered body whose relative density exceeded 98.9%. The lattice constant decreased from 1.0357 nm to 1.0336 nm as the Si content increased. When the Si doping content (y) exceeded 0.3, the decrease in the lattice constant was reduced and residual Si appeared. This established the solubility limit of Si at the Sb sites was y = 0.3. The Seebeck coefficient increased with the temperature and Si content, achieving a maximum value of 178 µVK-1 at 723 K for y = 0.3. For the specimens with y ≤ 0.2, the electrical conductivity increased with temperature, and then slightly decreased at temperatures higher than 623 K, while it gradually increased with temperature for the specimens with y ≥ 0.3. The electrical conductivity decreased as the Si content increased at a constant temperature and the highest electrical conductivity of (2.8-3.4) × 104 Sm-1 was obtained at 323–723 K for Cu12Sb3.9Si0.1S13. When y = 0.4, the electrical conductivity did not decrease further, which is related to the solubility limit of Si. The power factor reached a maximum value of 0.86 mWm-1K-2 at 723 K for Cu12Sb3.9Si0.1S13. As the Si content increased, the thermal conductivity tended to decrease, and Cu12Sb3.7Si0.3S13 exhibited the lowest thermal conductivity of 0.85 Wm-1K-1 at 723 K. Hence, the highest dimensionless figure of merit, ZT = 0.63 was achieved at 723 K for Cu12Sb3.8Si0.2S13.